Factors Determining Profit of Rubber and Oil Palm Smallholders in Batanghari, Jambi - Dewi, Triana Gita; Nurmalina, Rita; Rifin, Amzul (Pusat Penelitian dan Pengembangan Perkebunan, 2013)
scarcity causes the competition of land use for rubber and oil palm plantation. Hence, the decision of land use is based on the differences of profit. The higher profits, the higher incentive to farmers for developing a commodity. Land scarcity also leads smallholders to improve both rubber and oil palm without use more land. Hence, it is important to analyze the determinant factors of profit in these commodities. Hence, the specific objectives were to identify factors determining rubber and oil palm smallholders profit in Batanghari, Jambi and to compare the profit generated by rubber and oil palm smallholder. Survey method was conducted from October to December 2012 through direct observation and interview techniques. Analysis method used in this research is ordinary least square (OLS) where this method is developed in two regression models and descriptive analysis. The results show that in rubber plantation, factors determining profit are land size, tree age, number of productive tree, district, farmer age, herbicide, and labor, while in oil palm plantation, factors influencing profit are tree age, number of productive tree, district, NPK, and herbicide. Based on average profit generated in planted period, oil palm plantations is more profitable than rubber plantation, they are Rp. 9.387.561,00 and Rp. 8.763.116,00 per ha per year, respectively.Karet, kelapa sawit, ordinary least square, labaÂ